Consumers' Perception of Islamic Credit Cards: An Exploratory Study - Johan, ZJ; Hussain, MZ; Putit, L; Dali, NRSM; Hafit, NIA (Univ Putra Malaysia Press, 2024)
The growth and development of Islamic finance in Malaysia vis-a-vis the conventional finance has been supported by the comprehensive regulatory framework and a conducive environment. Despite the favourable operating environment, and commendable performance of certain Islamic financial products and services, a majority of financial services consumers is still pursuing conventional banking products. Their lack of acceptance of Shariah compliant banking products is attributable to many factors; including lack of knowledge and awareness of Shariah compliant issues, which has given rise to scepticism and continued misperception of the products as well as bankers' approaches to product and market development of Islamic financial products and services. This exploratory study is aimed at identifying consumer acceptance of Islamic Credit Cards (ICCs) and the determinants of their acceptance. The variables tested were attitude, knowledge, perceived benefits, brand reputation and Shariah compliance. Since Islamic banking products are meant for all, it is timely to highlight the focal point of Shariah compliance as the main attribute. This study also provides further insights into understanding consumers' acceptance of ICCs.